PROPAGANDA SURAT KHABAR HARIAN RAKJAT SEMASA KONFRONTASI INDONESIA-MALAYSIA, 1963–1965 (Propaganda of Harian Rakjat Newspaper During the Indonesia-Malaysia Confrontation, 1963-1965) (Applied History Journal of Merong Mahawangsa, 2023)
ABSTRAKKajian ini bertujuan untuk meninjau kegiatan propaganda surat khabar Harian Rakjat yang diterbitkan oleh Partai Komunis Indonesia (PKI) semasa Konfrontasi Indonesia-Malaysia pada tahun 1963 sehingga 1965. Tujuan kajian ini adalah melihat sejauhmana PKI memanfaatkan surat khabar Harian Rakjat untuk menyebarkan propangada untuk meraih sokongan rakyat mengganyang Malaysia. Strategi PKI menggunakan propaganda melalui tulisan dan karikatur dilihat telah berjaya menyemai kebencinan rakyat terhadap pemimpin dan rakyat Malaysia. Kajian ini menggunakan metodologi pengumpulan data melalui kaedah kepustakaan. Kajian perpustakaan ditumpukan kepada penggunaan dokumen-dokumen surat khabar terbitan Parti Komunis Indonesia yang tersimpan di Perpustakaan Nasional Republik Indonesia dan kajian lapangan seperti temubual dan pemerhatian. Hasil kajian menunjukkan bahawa propaganda Parti Komunis Indonesia menggunakan surat khabar, baik melalui tulisan-tulisan mahupun penggunaan karikatur telah berjaya mempengaruhi rakyat Indonesia untuk menyokong dasar politik konfrontasi Presiden Sukarno terhadap Malaysia. Sokongan rakyat ini diterjemahkan melalui sambutan rakyat terhadap kempen Mengganyang Malaysia yang dilaungkan oleh Presiden Sukarno.ABSTRACTThis research aimed to review the propaganda activities involved in the Harian Rakjat newspaper which was published by the Indonesian Communist Party (PKI) during the Indonesia-Malaysia Confrontation between 1963-1965. The main objective of this research was to discover how far PKI utilise the Harian Rakjat newspaper to spread propaganda in order to gain the Indonesia citizen’ support to (go against, criticise, destroy) Malaysia. PKI’s strategies spreading propaganda through caricature and writing were deemed successful in sowing hatred among Indonesian citizens towards Malaysian leader and citizens. This research employed the library research method in collecting data. The library research was centralized on the use of newspapers published by the Indonesian Communist Party which was kept at the National Library of Indonesia as well as through field studies which encompassed interviews and observations. The findings of this research had shown that the Indonesian Communist Party’s propaganda in utilising the newspaper either through writings or caricatures had successfully influenced Indonesian citizens to support Sukarno’s political confrontation towards Malaysia. This support was portrayed through the great responses from the Indonesian citizen on the “Mengganyang Malaysia campaign” masterminded and chanted by Sukarno.